Geology of Bajaur and Northern Part of Mohmand - Badshah, Mian Sayed (Journal of Himalayan Earth Sciences, 1979)
Geological investigation in about 1000 sq. km. of area in Bajaur and Ambhar Utmankhel reveal that the area falls in the western tip of Kohistan with the Main Mantal Thrust (MMT) running roughly east-west, following the course of Bajaur Khwar. The area is overlain by the tectonic slices which moved from NW to SE. The area exposes igneous and metamorphic rocks. Nawagai Limestone of (?) Silurian-Devonian age lies to the south-west. The pelitic sediments include amphibolites, epidote chlorite schists, phyllitic schists, piemontite schists, talc carbonate schists, graphite schists and slates. Extensive distribution of garnet schists is observed in the Shamozai area, lying to the southeast. The' igneous masses comprise granites and diorites; ultrabasic and volcanic rocks. The granitic and dioritic rocks are not considered to be comagmatic. The intrusion of diorites started sometimes in the Late Cretaceous, while the whole magmatism ended with the last phase of granitic stocks and dykes in Middle Eocene. The late Upper Cretaceous to Eocene-Oligocene ultrabasic phases of serpentinite, peridotite and pyroxenite/hornblendite lie "interbedded" with the metasediments. Eocene to Oligocene volcanic rocks of andesitic, rhyolitic and tuffaceous compositions are also present. Poor mineralization of copper, promising mineralizations of manganese, soapstone and chromite along with large deposit of marble are the noteworthy prospects in the area.